Evaluasi Kondisi Kerja Pada UMKM Pempek Menggunakan Work Improvement In Small Enterprises (Wise) - Saputra, Muhammad Egy; Kusmindari, Christofora Desi (Syntax Literate, 2023)
Pempek Ita is a MSMEs that produces several types of processed pempek products, based on the results of initial observations there are several problems in their working conditions and the absence of K3 implementation in the workplace. This study aims to improve the work system by evaluating the condition of Pempek Ita using the WISE checklist, then using the Borda method for decision making. The evaluation results from the WISE checklist contained 19 elements that required corrective action. By using the Borda method, it is obtained that decision making for the priority of improving the work system is the work organization because it has the highest weight, which is 23%. Then a proposal for improvement of the work system is made based on the criteria of the work organization, namely implementing a periodic rest schedule in accordance with Article 79 paragraph (2) letter a of Law no. 13/2003 stipulates that companies must provide rest periods between working hours, at least half an hour after workers have worked continuously for 4 hours and that rest time does not include working hours. And conduct training programs for employees regarding OHS. General OHS expert training (Indonesian Ministry of Manpower Certification) is a program of the Ministry of Manpower (KEMNAKER) to prepare OHS experts in companies who can help develop OHS in companies.